AN ANALYSIS OF ILLOCUTIONARY ACTS IN MICHELLE OBAMAS SPEECH AT THE 2020 DEMOCRATIC NATIONAL CONVENTION - Rahmania Novitasari; Ingatan Gulo (Linguistics and Literature Students' Journal, 2023)
Many speakers convey the message to make the speech partner do something according to what the speaker intended through his/her utterance, which is called an illocutionary speech act. This study aims to analyze the types and functions of illocutionary acts in Michelle Obama's speech at the 2020 Democratic National Convention. This study was conducted by using a qualitative method and the data is analyzed descriptively. the data is the utterances of Michelle Obama in her speech video at the 2020 Democratic National Convention which was transcribed into words. Data can be in the form of sentences uttered by the speaker. Assertive illocutionary acts were employed to convince the audience of the message conveyed, through actions such as stating, informing, claiming, expressing opinions, providing information, convincing, assessing, and describing. Directive illocutionary acts were used to influence the listener to take certain actions, such as through invitations, advice, and expressions of desire. On the other hand, expressive illocutionary acts were utilized to express emotions towards the actions of the listener and the situations at occur, such as expressing gratitude, appreciation, respect, and disappointment. This research provides a deeper understanding of the use of illocutionary acts in political speech and Michelle Obama's contribution to influencing and inspiring the audience.Keywords: Illocutionary acts, political speech, speech acts